Mathematical Modeling of Phase-Controlled Converters Considering Discontinuous Conduction Modes. Issue 12 (21st July 2017) - Afsharian Zadeh, Armin; Samani, Faramarz; Vahidi, Behrooz; Milimonfared, Jafar
Abstract: Despite possessing outstanding features, phase-controlled converters are also known for their control performance deterioration whenever their output currents become discontinuous. This paper aims to provide a mathematical framework to overcome converter input/output characteristic nonlinearities, arising from discontinuous current conduction regime. A secondary purpose is to expand the idea of Predictive Current Control (PCC) for phase-controlled converters, taking into account multiple discontinuous current conduction modes. To this end, starting with a detailed converter circuit analysis, equations describing boundaries between converter operating modes are derived and depicted as a graph. The resulted graph is utilized to devise an algorithm to identify mode of operation and to calculate firing angle corresponding to "desired average output voltage". Experiments in conjunction with simulation studies are conducted to evaluate the assumptions made, the equations derived, and the algorithm devised. Based on the proposed algorithm, two improvements on converter current control are achieved. Firstly; the transfer characteristic of the converter is linearized. Secondly; the PCC strategy, which has attracted much attention recently, is implemented in Single Phase Full Controlled (SPFC) converter. Moreover, the comprehensive treatment of all operating mode boundaries presented in this paper helps deepen physical insight into the SPFC converter operation.